Textos para la etnohistoria en la frontera dominicana de Baja California - Mixco, Mauricio J. (Tlalocan, 2013)
After the expulsion of the Jesuits in 1767 the Spanish government established a number of missions on what was known as the "Dominican Frontier" of the Peninsula of Lower California, among the Yuman peoples in the area of the Colorado River. The author, who has worked among the Pai Pai, presents and analyzes seven texts in that language. Most deal with the cosmological views of said Yuman group.